Validity and Practicality Electronic Pocketbook-Based Google Sites for High School Level - Misbahul Jannah; Mujibul Rijal; Muhammad Nasir (Postgraduate, University of Mataram, 2024)
This research addresses the limitations of textbook-centered learning resources, which hinder students' understanding of complex concepts and equations, particularly in the topics of sound and light waves. The study aims to develop, validate, and assess the practicality of an electronic pocketbook based on Google Sites for high school-level materials on sound and light waves. Employing the Research and Development (R&D) method, this study follows the Alessi and Trollip development model, consisting of Planning, Design, and Development phases. Expert validators in the fields of content, media, and language, along with feedback from 24 students and three teachers from Senior High School 9 Banda Aceh, were utilized to assess the pocketbook. Results show that the electronic pocketbook successfully completed all development stages and achieved high validity, with material validation at 95.29%, media validation at 91.90%, and language validation at 93.06%, all categorized as